2020
DOI: 10.1186/s10020-020-00250-7
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-199a-5p regulates epithelial-to-mesenchymal transition in diabetic cataract by targeting SP1 gene

Abstract: Background As a common ocular complication of diabetes mellitus, diabetic cataract is becoming a leading cause of visual impairment. The progression of diabetic cataract progression involves epithelial-to-mesenchymal transition (EMT), the precise role of which remains to be investigated. As microRNAs (miRNAs) are suggested to be involved in the pathogenesis of many diseases, identification of aberrantly expressed miRNAs in diabetic lens epithelial cells (LECs) and their targets may provide insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…The correlation between the EMT of LECs and diabetic cataracts has been reported (Zhang et al 2017; Du et al 2017 ; Liu et al 2020 ). We have also confirmed that high-glucose stimulation induces the EMT of LECs in vitro (Han et al 2018 ; Li et al 2020 ; Ye et al 2020 ).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…The correlation between the EMT of LECs and diabetic cataracts has been reported (Zhang et al 2017; Du et al 2017 ; Liu et al 2020 ). We have also confirmed that high-glucose stimulation induces the EMT of LECs in vitro (Han et al 2018 ; Li et al 2020 ; Ye et al 2020 ).…”
Section: Discussionmentioning
confidence: 86%
“…Autophagy is essential for maintaining the homeostasis of cells, tissues and organs (Dikic and Elazar 2018 ), especially in the eye, including the cornea, retina, and lens (Chai et al 2016 ). Impairment of autophagy flux in LECs and fiber cells may result in the formation of congenital cataracts, age-related cataracts, and diabetic cataracts (Morishita et al 2013 ; Liu et al 2020 ; Andley and Goldman 2016 ). In the present study, autophagic activity was attenuated both in LECs of diabetic rats and in HLE-B3 cells stimulated with high glucose concentrations, consistent with the findings of many other studies (Chen et al 2021 ; Li et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…of sorbitol, galactitol and advanced glycation end products (AGEs), and oxidative stress damage activated by reactive oxygen species (ROS). [21][22][23][24] At present, the effective treatment for various types of cataracts is still surgery, and there is still no medicine that can effectively inhibit or delay the occurrence and development of DC. The reason is that the purification methods of the drugs studied in these experiments are not uniform, or the way of action of drugs on diabetic cataract is relatively single, so it may be weak for the drugs on the effect of diabetic cataract with complex pathogenesis in actual clinical conditions.…”
mentioning
confidence: 99%